Essence of networking - Eswaran, Vijay, Dato'; Balagtas,Chandravali Dasi; Munian, Maralikrishnan; VStudios ([S.l.] : VStudios, 2008)
A talk by Dato' Vijay Eswaran at Bangkok on 2005. A talk on the essece of social networking or multilevel marketing in this new era
Title from title screen
V-Thailand
Executive producer, Pathman Senathirajah
DVD format
Keywords: Multilevel marketing; Direct marketing